Cultural Communication and Food Self-Reliance among the Samin Community in Blora, Indonesia - Agung Wibowo; Waskito Widi Wardojo; Andre Noevi Rahmanto; Rosita Candrakirana (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
This study examines how cultural communication sustains food self-reliance among the Samin community in Blora Regency, Central Java, Indonesia. Using a qualitative case study approach, data were collected from 12 purposively selected participants — comprising traditional elders (sesepuh) and active community members — until thematic saturation was reached, through in-depth interviews, participant observation of agricultural practices and ritual ceremonies, and documentation of oral traditions. Thematic analysis reveals that cultural communication operates through three interconnected mechanisms: the intergenerational transmission of ecological agricultural knowledge (land management, seed selection, and planting cycles), cooperative social norms (gotong royong and deliberation) that govern collective land management and harvest distribution, and ritual practices that reinforce the community's moral framework regarding human–nature relations. Together, these mechanisms constitute a locally embedded system of food governance that reduces external dependency and sustains food self-reliance. Rather than portraying the community as uniformly resistant to modernization, this study finds that the Samin community exercises selective engagement with external interventions, prioritizing practices that align with their socio-cultural values. The central analytical contribution of this study is the conceptualization of cultural communication as a form of indigenous food governance one that warrants formal recognition in the design of culturally sensitive and sustainable food self-reliance policies.